A Study of optical, structural and electrical properties of copper oxide films prepared by chemical bath deposition with laser at different concentrations - Mohammed A. Jabr; Abdullah M. Ali; Raid A. Ismail (Tikrit Journal of Pure Science)
In this study, a copper oxide (CuO) thin film was prepared by the (Continuous-Wave) CW laser assisted-chemical bath deposition (LACBD) technique. The effect of laser wavelength on the structural, optical, and electrical properties of CuO film was investigated. The X-ray diffraction (XRD) study showed that the deposited CuO films were crystalline with a monoclinic structure. The optical energy gap increased with the use of a laser during film preparation and it varied from 2.3 to 1.8 eV. The scanning electron microscope (SEM) images confirmed that the film morphology was dependent on the laser wavelength. Increasing the laser wavelength resulted in decreasing the granule size of the film, which enhanced the crystallization. Energy dispersive X-ray (EDX) analysis confirmed the presence of copper and oxygen elements.  Hall measurement revealed that the deposited films were p-type and the electrical conductivity and mobility increased with the use of a laser. The current-voltage characteristics of the p-CuO/p-Si heterojunction were studied in the dark and under illumination. The maximum optical current of the prepared photodetector at a laser wavelength of 550 nm was found to be in the order of 1.59 × 1012 cm.Hz1/2.W-1. The spectral responsivity revealed that the photodetectors exhibited two peaks of response at 450 nm and 800 nm. The maximum responsivity reached was 0.48 A/W at 450 nm and 0.53 A/W at 800 nm for a photodetector prepared at the laser wavelength of 550 nm.